The Emergence of Modern Hinduism Religion on the Margins of Colonialism - Weiss, Richard S. (University of California Press, 2019)
The Emergence of Modern Hinduism argues for the importance of regional, vernacular innovation in processes of Hindu modernization. Scholars usually trace the emergence of modern Hinduism to cosmopolitan reform movements, highlighting the centrality of elite religion and the influence of Western ideas and models. This book proposes, instead, that important projects of modernity were pursued on the colonial margins, by actors deeply embedded in tradition and deploying all its resources as the key means for change, using texts and languages not associated with centralized power or national or global discourses. It focuses on one such figure, the Tamil Shaiva poet and mystic Ramalinga Swami (1823-1874). Ramalinga emphasized the continuities of tradition, new revelation, the possibility of the miraculous, and an ethics of inclusion that challenged caste and class boundaries. His vision provided a counterpoint to reform Hinduism, yet his projects were no less modern than their cosmopolitan counterparts. By including Ramalinga, and figures like him, in historical accounts of religious modernization, we can develop new ways of thinking about modern Hinduism that more accurately reflect its diverse ways of being modern. The book thus effects a fundamental shift in the way we conceptualize the emergence of modern religion, as well as the concept of the "modern" itself, in South Asia and beyond.